2019
DOI: 10.1148/radiol.2019181695
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for Early-Phase Diffuse Idiopathic Skeletal Hyperostosis: Development and Validation

Abstract: iffuse idiopathic skeletal hyperostosis (DISH) is a condition characterized by the formation of new bone along the anterolateral spinal column (1). The lower thoracic spine is most frequently affected, and ossifications of peripheral entheses are also frequently present in DISH (1,2). The prevalence of DISH varies between 2.9% and 42.0%, depending on the criteria used, demographic background, and presence of associated factors (3-6). Risk factors for developing DISH are older age, metabolic derangement (hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 14 publications
0
36
0
1
Order By: Relevance
“…Fifth, concurrent pathology such as diffuse idiopathic skeletal hyperostosis may aggravate OA scores. Grading systems for such concurrent diseases could be used along with the OA scores to further characterize individuals [ 37 , 38 , 39 ]. Sixth, CT involves exposure to possibly harmful ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, concurrent pathology such as diffuse idiopathic skeletal hyperostosis may aggravate OA scores. Grading systems for such concurrent diseases could be used along with the OA scores to further characterize individuals [ 37 , 38 , 39 ]. Sixth, CT involves exposure to possibly harmful ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Resnick et Nivayama, 1976, described the changes found by CR in patients with DISH and demonstrated that the disease is not limited to the spine [15]. In subsequent years, these findings were confirmed by other authors [16][17][18][19][20][21]. The authors note that changes initially occur in the lower right thoracic segment (around Th 9, 8, 7, 10).…”
mentioning
confidence: 78%
“…Criteria for diagnosis in research and clinical settings are controversial. In the research setting, it is recommended to completely exclude DISH cases from patients with comorbidities described in the Resnick and Niwayam exclusion criteria [ 4 , 58 ].…”
Section: Clinical Aspectsmentioning
confidence: 99%